Comprehensive overview of different medicinal parts from Morus alba L.: chemical compositions and pharmacological activities - Wang, Yumei; Ai, Qing; Gu, Meiling; Guan, Hong; Yang, Wenqin; Zhang, Meng; Mao, Jialin; Lin, Zhao; Liu, Qi; Liu, Jicheng (Frontiers in Pharmacology, 2024)
Morus alba L., a common traditional Chinese medicine(TCM) with a centuries-old medicinal history, owned various medicinal parts like Mori folium, Mori ramulus, Mori cortex and Mori fructus. Different medical parts exhibit distinct modern pharmacological effects. Mori folium exhibited analgesic, anti-inflammatory, hypoglycemic action and lipid-regulation effects. Mori ramulus owned anti-bacterial, anti-asthmatic and diuretic activities. Mori cortex showed counteraction action of pain, inflammatory, bacterial, and platelet aggregation. Mori fructus could decompose fat, lower blood lipids and prevent vascular sclerosis. The main chemical components in Morus alba L. covered flavonoids, phenolic compounds, alkaloids, and amino acids. This article comprehensively analyzed the recent literatures related to chemical components and pharmacological actions of Morus alba L., summarizing 198 of ingredients and described the modern activities of different extracts and the bioactive constituents in the four parts from Morus alba L.. These results fully demonstrated the medicinal value of Morus alba L., provided valuable references for further comprehensive development, and layed the foundation for the utilization of Morus alba L..